2016
DOI: 10.1038/srep37278
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat High-Sucrose Diet Rapidly Alters Muscle Integrity, Inflammation and Gut Microbiota in Male Rats

Abstract: The chronic low-level inflammation associated with obesity is known to deleteriously affect muscle composition. However, the manner in which obesity leads to muscle loss has not been explored in detail or in an integrated manner following a short-term metabolic challenge. In this paper, we evaluated the relationships between compromised muscle integrity, diet, systemic inflammatory mediators, adipose tissue, and gut microbiota in male Sprague-Dawley rats. We show that intramuscular fat, fibrosis, and the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 37 publications
0
80
1
3
Order By: Relevance
“…To assess the relationship between gut microbiota, inflammation, and muscle composition, Collins et al subjected young rats to a high-fat high-sucrose diet and found an increase in Enterobacteriaceae (gram-negative member of the Proteobacteria phylum) and a decrease in the abundance of Lactobacillus spp ., changes that have been similarly reported with aging [83, 84]. Concomitant with these changes, the authors reported an increase in circulating inflammatory cytokines (IL-6, TNF-α, and MCP-1) and intramuscular fat after just 3 days [85], suggesting rapid dysregulation of these seemingly inter-connected systems. Regulation of muscle composition by gut microbiota is supported by associations between gut bacteria involved in energy metabolism and porcine intramuscular fat content [86].…”
Section: Gut Microbiota and Skeletal Muscle Size Composition And Fumentioning
confidence: 68%
“…To assess the relationship between gut microbiota, inflammation, and muscle composition, Collins et al subjected young rats to a high-fat high-sucrose diet and found an increase in Enterobacteriaceae (gram-negative member of the Proteobacteria phylum) and a decrease in the abundance of Lactobacillus spp ., changes that have been similarly reported with aging [83, 84]. Concomitant with these changes, the authors reported an increase in circulating inflammatory cytokines (IL-6, TNF-α, and MCP-1) and intramuscular fat after just 3 days [85], suggesting rapid dysregulation of these seemingly inter-connected systems. Regulation of muscle composition by gut microbiota is supported by associations between gut bacteria involved in energy metabolism and porcine intramuscular fat content [86].…”
Section: Gut Microbiota and Skeletal Muscle Size Composition And Fumentioning
confidence: 68%
“…Serum samples were prepared and analyzed for LPS and protein as previously described (2224). Twenty‐seven markers were quantified in serum using a rat 27‐plex assay and LuminexxMAP technology (Eve Technologies, Calgary, AB, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…This compromise in muscle integrity can be observed at very early time points, as early as 3 days on HFS, and appears to be sustained in glycolytic skeletal muscles (Collins et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies detailing short‐term and long‐term responses in oxidative soleus muscle integrity to metabolic challenge are lacking (Collins et al. ). Although many previous studies aimed at producing muscle atrophy (denervation, casting, hind limb suspension) in the soleus muscle (Bodine et al.…”
Section: Introductionmentioning
confidence: 99%